Let $A$ and $E$ be opposite vertices of an octagon. A frog starts at vertex $A.$ From any vertex except $E$ it jumps to one of the two adjacent vertices. When it reaches $E$ it stops. Let $a_n$ be the number of distinct paths of exactly $n$ jumps ending at $E$. Prove that: \[ a_{2n-1}=0, \quad a_{2n}={(2+\sqrt2)^{n-1} - (2-\sqrt2)^{n-1} \over\sqrt2}. \]
Problem
Source: IMO ShortList, The Democratic Republic Of Germany 3, IMO 1979, Day 2, Problem 6
Tags: combinatorics, recurrence relation, Linear Recurrences, counting, IMO, IMO 1979
25.12.2006 09:51
Anyone with a solution
25.12.2006 16:31
Ummm... isn't it pretty easy by recursion? Just consider the # of ways of landing on B, D, F, and H in an odd number of steps. Edit: Ermmm yes I meant recurrence , although it is a type of recursion
25.12.2006 16:42
probability1.01 wrote: Ummm... isn't it pretty easy by recursion? Just consider the # of ways of landing on B, D, F, and H in an odd number of steps. Recurrence you mean. And yes you don't need anything else.
25.12.2006 19:46
If wiequan and probability1.01 have better things to do, then i will post my solution First the part $a_{2n-1}=0$ It's preety obvious. Let's make a sequence $b$ of 1 and -1, setting 1 when the frog jumps left and -1 when it jumps right. If the frog would want to come to vertex E from vertex A, then $\sum b_{i}$ from $i =1$ to $i =2n-1$ should be equeal to either 4 or -4. But this sum is odd, so we have $a_{2n-1}= 0$ Now the less obvious part. Let's name $f(X,y)$ the number of ways, in which we can come to vertex X in y moves. Then $f(E,2n) = f(F,2n-1)+f(D, 2n-1) = f(C, 2n-2)+f(G, 2n-2) =$ $f(D, 2n-3)+f(B, 2n-3)+f(F, 2n-3)+f(H, 2n-3) =$ $2f(D, 2n-5)+2f(F, 2n-5)+4f(H,2n-5)+4f(B, 2n-5) =$ $4[ f(B,2n-5)+f(D, 2n-5)+f(F,2n-5)+f(H, 2n-5) ]-2 [ f(F,2n-5)+f(D,2n-5)] =$ $4f(E,2n-2)-2f(E,2n-4)$ Now we can find a solution to this reccurenc or simply prove by induction the given answer. I didn't explain to much because I'm lazy, but I hope everything's clear.
16.04.2022 17:58
It's my first IMO combinatorics solution. There's some mystery about counting problems having being lengthy solution. Anyway let's post the solution.
16.04.2022 18:45
$\text{Let }a_n, b_n, c_n, d_n, e_n, f_n, g_n, h_n,$ be the number of exactly $n$, distinct paths of jump ending at the points $A,B,C,D,E,F,G,H$ of the octagon respectively. By symmetry we have, $b_n=h_n, c_n=g_n, d_n=f_n.$ We also have \begin{align*} e_n=d_{n-1} +f_{n+1}=2d_{n-1}, \\ d_n=c_{n-1}, c_n=b_{n-1}+d_{n-1}, \\ a_n=2b_{n-1}, b_n=a_{n-1}+c_{n-1}. \end{align*}From the first two we get $d_{n-1}=e_n/2$ and $c_{n-1}=d_n=e_{n+1}/2.$ Subbing into the third we get $b{n-1}=1/2(e_{n+2}-e_n).$ From the fourth, $a_n=e_{n+2}-e_n.$ The fifth will be $$e_{n+3}-4e_{n+4}+2e_{n-1}=0.$$ Now from a well known result in recursion we have, $$e_n=as^n+b(-s)^n+cr^n+d(-r)^n,$$where $s=\sqrt{2+\sqrt{2}}$ and $r=\sqrt{2-\sqrt{2}}.$ It follows that $e_1=e_2=e_3=0$, and $e_4=2.$ And therefore, \begin{align*} (a-b)s+(c-d)r=0, \\ (a+b)s^2+(c+d)r^2=0, \\ (a-b)s^3+(c-d)r^3=0, \\ (a+b)s^4+(c+d)r^4=2.\end{align*}The first and third equations imply $a=b$ and $c=d$ which further imply $e_{2n-1}=0.$ Solving the second and fourth equations we get $$a=b= \frac{r^2}{4\sqrt{2}}, c=d=-\frac{s^2}{4\sqrt{2}}.$$ Finally we have, $$e_{2n}=2as^{2n}+2cr^{2n}=\frac{s^2r^2}{2\sqrt{2}} (s^{2n-2}-r^{2n-2})=\frac{(2+\sqrt{2})^{n-1} -(2-\sqrt{2})^{n-1}}{\sqrt{2}}.$$$\text{Q.E.D.}$ P.S: @above I find no implication of your post except pure nonsense, you might want to redact such spamful message.
Attachments:

16.04.2022 19:49
ZETA_in_olympiad wrote: $\text{Let }a_n, b_n, c_n, d_n, e_n, f_n, g_n, h_n,$ be the number of exactly $n$, distinct paths of jump ending at the $8$ points of the octagon respectively. By symmetry we have, $b_n=h_n, c_n=g_n, d_n=f_n.$ We also have \begin{align*} e_n=d_{n-1} +f_{n+1}=2d_{n-1}, \\ d_n=c_{n-1}, c_n=b_{n-1}+d_{n-1}, \\ a_n=2b_{n-1}, b_n=a_{n-1}+c_{n-1}. \end{align*}From the first two we get $d_{n-1}=e_n/2$ and $c_{n-1}=d_n=e_{n+1}/2.$ Subbing into the third we get $b{n-1}=1/2(e_{n+2}-e_n).$ From the fourth, $a_n=e_{n+2}-e_n.$ The fifth will be $$e_{n+3}-4e_{n+4}+2e_{n-1}=0.$$ Now from a well known result in recursion we have, $$e_n=as^n+b(-s)^n+cr^n+d(-r)^n,$$where $s=\sqrt{2+\sqrt{2}}$ and $r=\sqrt{2-\sqrt{2}}.$ It follows that $e_1=e_2=e_3=0$, and $e_4=2.$ And therefore, \begin{align*} (a-b)s+(c-d)r=0, \\ (a+b)s^2+(c+d)r^2=0, \\ (a-b)s^3+(c-d)r^3=0, \\ (a+b)s^4+(c+d)r^4=2.\end{align*}The first and third equations imply $a=b$ and $c=d$ which further imply $e_{2n-1}=0.$ Solving the second and fourth equations we get $$a=b= \frac{r^2}{4\sqrt{2}}, c=d=-\frac{s^2}{4\sqrt{2}}.$$ Finally we have, $$e_{2n}=2as^{2n}+2cr^{2n}=\frac{s^2r^2}{2\sqrt{2}} (s^{2n-2}-r^{2n-2})=\frac{(2+\sqrt{2})^{n-1} -(2-\sqrt{2})^{n-1}}{\sqrt{2}}.$$$\text{Q.E.D.}$ P.S: @above I find no implication of your post except pure nonsense, you might want to redact such spamful message. Wow nice solution! Seems right to me. How did you motivate the definitions of \(a_n\), \(b_n\), \(c_n\), etc though?
17.04.2022 06:49
rama1728 wrote: Wow nice solution! Seems right to me. How did you motivate the definitions of \(a_n\), \(b_n\), \(c_n\), etc though? Do you want the picture of the octagon? I added the motivation picture. P.S. Please try to keep quotations short.